Vox on the Rocks - Haywood, N (University of Tasmania, Conservatorium of Music Recital Hall, 2012)
This project saw the collaboration between the Conservatorium of Music and IMAS. Nick Haywood features as a member of an improvised music ensemble that performed real time interpretations of graphic representations of data sets collected from a variety of Antarctic studies associated with seal migration. The ensemble also featured Nick Haywood, Andrew Legg and Glen Hodges.